Travel-related infections in mainland China, 2014–16: an active surveillance study. (August 2018) - Fang, Li-Qun; Sun, Yu; Zhao, Guo-Ping; Liu, Li-Juan; Jiang, Zhe-Jun; Fan, Zheng-Wei; Wang, Jing-Xue; Ji, Yang; Ma, Mai-Juan; Teng, Juan; Zhu, Yan; Yu, Ping; et al.
Summary: Background: Transmission of infection through international travel is a growing health issue, and the frequency of imported infection is increasing in China. We aimed to quantify the total number of infections imported into mainland China by arriving travellers. Methods: We actively surveyed arriving travellers at all 272 international entry–exit ports in mainland China. Suspected cases were detected through fever screening, medical inspection, self-declaration, and reporting by on-board staff. Participants completed a standardised questionnaire with questions about demographics, their travel itinerary (including detailed information about all countries or regions visited), and clinical manifestations. Nasopharyngeal swabs, sputum samples, faecal samples, vomitus, blood, and serum were collected as appropriate for diagnoses. Diagnosis was made by specific laboratory tests according to the national technical guidelines. Infections were classified as respiratory, gastrointestinal, vector-borne, blood-transmitted and sex-transmitted, or mucocutaneous. We divided arriving travellers into two groups: travellers coming from countries other than China, and travellers coming from Hong Kong, Macau, and Taiwan. We integrated surveillance data for 2014–16, calculated incidences of travel-related infections, and compared the frequency of infections among subgroups. Findings: Between Jan 1, 2014, and Dec 31, 2016, 22 797 cases were identified among 805 993 392 arriving travellers—an overall incidence of 28·3 per million. 45 pathogens were detected in participants: 18 respiratory (19 662 cases), ten gastrointestinal (189 cases), seven vector-borne (831 cases), seven blood-transmitted and sex-transmitted (1531 cases), and three mucocutaneous (584 cases). Both the overall number and incidence of infection were more than five times higher in 2016 than in 2014. Case numbers and incidences also varied substantially by province, autonomous region, and municipality. Overall, 17 643 (77%) infections were detected by fever screening, but 753 (49%) blood-transmitted and sex-transmitted infections were identified through medical inspection. 14 305 (73%) cases of respiratory infection and 96 (51%) of gastrointestinal infections were in tourists. Tuberculosis, hepatitis A virus, vector-borne, and blood-transmitted and sex-transmitted infections were common among Chinese labourers who worked abroad. Dengue and malaria were most commonly diagnosed in travellers arriving from Africa. 12 126 (93%) of the 12 985 cases arriving from Hong Kong, Macau, or Taiwan were respiratory infections. Hand, foot, and mouth disease accounted for 2·90% of infections in travellers from Hong Kong, Macau, or Taiwan and 0·31% of infections in international travellers. Interpretation: This report is the first to characterise the profile of travel-related infections among arriving travellers in mainland China. Our findings should increase public awareness of the potential risk of imported infections, and help health-care providers to make evidence-based health recommendations to travellers. Funding: The Natural Science Foundation of China.